SPECT/CT and fusion ultrasound to target the efferent groin lymph node for lymphatic surgery. Issue 7 (10th August 2019) - Gentileschi, Stefano; Albanese, Roberta; Pino, Valentina; Stefanizzi, Gianluigi; Fragomeni, Simona; Zagaria, Luca; Ieria, Francesco P.; Salgarello, Marzia; Scambia, Giovanni; Garganese, Giorgia
Abstract: Introduction: Pelvic lymphadenectomy (PL) causes changes to the inguinal lymph nodes with progressive loss of immune and lymphatic pump function. Efferent lymphatic vessel‐to‐venous anastomosis (ELVA) has been reported to address this problem. The aim of this report was to describe the feasibility of the SPECT/CT combined with ultrasound fusion imaging (UFI) to target the groin efferent lymph node (GELN) for ELVA. Patients and Methods: Twelve patients with lower limb lymphedema after PL were scheduled for peripheric lymphaticovenular anastomosis (LVA) combined with ELVA. All‐patients were clinically ISL‐stage1, with good visualization of the inguinal lymph nodes at preoperative lymphoscintigraphy. The mean patient age was 55.4 years and the mean BMI was 25.5.The mean limb circumference (MLC) was calculated before surgery and 1 year after surgery. The LymQoL‐Leg questionnaire was administered before surgery and 6 months after surgery. Before surgery, the GELN was identified by SPECT/CT and its location was marked on the skin by UFI virtual navigation. Peripheric LVA sites were planned by ultrasound and indocyanine green (ICG) lymphography. Pre and postoperative MLC and LymQoL‐Leg scores were compared. Results: In all‐patients, the SPECT/CT succeeded at detecting and targeting the GELN. In all‐patients, real‐time anatomical coregistration with US was feasible, and it was possible to mark on the groin skin the depth and position of the GELN on the skin at the groin. During surgery, in every patient, we found the GELN marked before surgery and performed ELVA. We also performed two or three peripheric LVAs in every patient. The mean value of MLC decreased (38.2 ± 2.13 cm vs. 36.33 ± 2.14 cm; p = .04) and the mean score of the LymQoL‐Leg questionnaire improved (9.3 ± 1.7 vs. 7.7 ± 1.1; p = .02). Conclusion: SPECT/CT combined with UFI is feasible for the preoperative identification of GELN for ELVA.